Clínicas de derecho como un elemento importante en la defensa gratuita de los derechos humanos - Serhii Kivalov (Ius Humani. Jornal do direito, 2019)
Nowadays, legal clinics exist in almost every country in the world. The article examines the legal status of legal clinics in Ukraine to properly ensure the human right to legal aid. The author emphasizes that legal clinics are an important element of the legal aid institute. Accordingly, there is an urgent need to regulate the legal status of legal clinics, since in this way the state fulfills its obligation to guarantee the constitutional right of every person to receive legal aid. Even though legal clinics perform important social tasks, regulatory regulation of their activity is carried out only at the level of acts of the Ministry of Education and Science of Ukraine. All attempts to consolidate the legal status of legal clinics at the level of the law—for example, the Law “On Free Legal Aid” of June 2, 2011—remain unrealized. The author states that the issue of improving the legal regulation of relations involving legal clinics should be resolved in the near future. Moreover, the Verkhovna Rada (Ukrainain Parlament) has recently started reforming its legislation in the field of advocacy. Therefore, there is a chance that the discriminatory norm of the Constitution regarding the lawyer’s monopoly on representation in court will be abolished. Thus, this will open the way to improving the status of legal clinics, as employees of such institutions will have the opportunity, in addition to legal advice, to represent their clients in court.